Transeuntes sobre ruínas: figurações alegóricas da casa familiar, no limiar de um certo exílio - Vieira, Noemi Campos Freitas [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The current study focuses on the investigation of allegorical aspects of family house in Milton Hatoum novels, The brothers (2000) and Ashes of the Amazon (2005). What is sought, in this work, is to undertake a reading of expressive allegory, in other words, open to a interpretative critical demand, which does not come, as we know, to solve the issues set out in the novels. According to Walter Benjamin, the criticism of the work is his mortification (cf. BENJAMIN, 2004, p. 197); according to this assumption, the literary work can be read and resignified allegorically (cf. BENJAMIN, 1984, p. 40), fitting to the critical and reflexive exercise reveal these contradictions through the allegorical reading of the family house. Allegory’s theory, developed by Benjamin, promotes a reflection about loss and attempted expression of unspeakable, through the literary language, thinking of allegorical as a dialectical and deviant discourse, which escapes historical linearity, being, therefore, contingent, as opposed to the timeless character that is assigned to the symbol. Milton Hatoum’s work, focused on raising questions about what is properly human, replaces the confrontation with the complexity of the drift and discontinuities, having, in the nuclear family, recurrent in his work, the confluence point of this complexity, for it is the “birthplace” from where radiate relations with the “other”. The house, recurrent term in the analysis, will be seen taking by resignifications, whose developments intend to point to three vertices intimately connected: allegory, memory and exile. Since this house is searched through memory, its fragmented recovery metaphorizes the subject’s self dilution that wants to achieve her. In the search for the origins, this subject finds himself exiled in an engendered dimension by memories and forgetfulness. The dialectical game between detachment and closeness, announcement and secret, latent and apparent, ...

O presente estudo tem como foco a investigação de aspectos alegóricos da casa familiar nos romances Dois irmãos (2000) e Cinzas do Norte (2005) de Milton Hatoum. O que se procura, neste trabalho, é empreender uma leitura da alegoria expressiva, ou seja, aberta a uma demanda crítica interpretativa, e que não vem, sabemos, para resolver as questões expostas nos romances. Segundo Walter Benjamin, a crítica da obra é a sua mortificação (cf. BENJAMIN, 2004, p. 197); segundo esse pressuposto, a obra literária pode ser lida e ressignificada alegoricamente (cf. BENJAMIN, 1984, p. 40), cabendo ao exercício crítico e reflexivo desvelar essas contradições por meio da leitura alegórica da casa familiar. A teoria da alegoria, desenvolvida por Benjamin, promove uma reflexão sobre a perda e a tentativa de expressão do indizível, por meio da linguagem literária, pensando no alegórico como discurso dialético e desviante, que escapa à linearidade histórica, sendo, portanto, contingencial, em oposição ao caráter atemporal atribuído ao símbolo. A obra de Milton Hatoum, voltada para o levantamento de questões sobre o que é propriamente humano, recoloca o confronto com a complexidade da deriva e das descontinuidades, tendo, no núcleo familiar, recorrente em sua obra, o ponto de confluência dessa complexidade, pois é o “lugar natal” de onde se irradiam as relações com o “outro”. A casa, termo recorrente nas análises, se verá tomada por ressignificações, cujos desdobramentos pretendem apontar para três vértices intimamente conectados: alegoria, memória e exílio. Sendo essa casa buscada por meio da memória, sua recuperação fragmentada metaforiza a própria diluição do sujeito que a ela quer alcançar. Na busca pela origem, esse sujeito se encontra exilado em uma dimensão engendrada pelas lembranças e pelo esquecimento. O jogo dialético entre distanciamento e aproximação, anúncio e segredo, o latente e o ...
Keywords: Hatoum, Milton 1952- Dois irmãos Cinzas do Norte Crítica e interpretação; Literatura brasileira; Ficção brasileira - História e crítica; Simbolismo na literatura; Brazilian fiction